Bacterial microcompartments in food-related microbes. (February 2022) - Zeng, Zhe; Dank, Alexander; Smid, Eddy J.; Notebaart, Richard A.; Abee, Tjakko
Abstract : Bacterial microcompartments (BMCs) are protein-based organelles that enhance a variety of metabolic functions in diverse bacteria and recent studies unveiled the importance of BMCs in bacterial adaptation from foods to gut. Comparative whole genome sequencing has shown a broad distribution of BMC-dependent metabolic pathways, but studies addressing the role of BMCs in food-related microbes are scarce. Recently, new insights have been reported on roles of BMC-dependent ethanolamine ( eut ) and propanediol utilization ( pdu ) in the notorious foodborne pathogen Listeria monocytogenes and the beneficial bacterium Propionibacterium freudenreichii . Notably, ethanolamine and the food additive 1, 2-propanediol are both abundant in foods and the gastrointestinal (GI) tract. Here we discuss the presence and implications of BMCs in both pathogenic and beneficial bacteria related to food.